Co-Administration of Lactulose Crystals with Amoxicillin Followed by Prolonged Lactulose Treatment Promotes Recovery of the Human Gut Microbiome In Vitro - Cindy Duysburgh; Pieter Van den Abbeele; Dennis Franckenstein; Martin Westphal; Angelika Kuchinka-Koch; Massimo Marzorati (MDPI AG, 2022)
The validated SHIME model was used to assess the effect of repeated administration of two different lactulose dosages (5 g/d and 10 g/d) on the human gut microbiome during and following amoxicillin-clavulanic acid treatment. First, antibiotic treatment strongly decreased Bifidobacteriaceae levels from 54.4% to 0.6% and from 23.8% to 2.3% in the simulated proximal and distal colon, respectively, coinciding with a marked reduction in butyrate concentrations. Treatment with lactulose enhanced acetate and lactate levels during antibiotic treatment, likely through lactulose fermentation by Lachnospiraceae and Lactobacillaceae. One week after cessation of antibiotic treatment, Bifidobacteriaceae levels re-increased to 20.4% and 7.6% in the proximal and distal colon of the 5 g lactulose/d co-administered unit, as compared with 1.0% and 2.2% in the antibiotic-treated unit, and were even further stimulated upon extension of lactulose administration. Marked butyrogenic effects were observed upon prolonged lactulose supplementation, suggesting the establishment of cross-feeding interactions between Bifidobacteriaceae and butyrate producers. Furthermore, a limited Enterobacteriaceae outgrowth following antibiotic treatment was observed upon dosing with 10 g lactulose/d, indicating inhibition of pathogenic colonization by lactulose following antibiotic therapy. Overall, lactulose seems to be an interesting candidate for limiting the detrimental effects of amoxicillin-clavulanic acid on the human gut microbiome, though further studies are warranted to confirm these findings.